Optimizing the Role of Hospital Health Promotion in Improving Superior Services - Fansuri, Muhaimin; Setiaji, Bambang; Karyus, Aila; Budiati, Endang; Irianto, Sugeng Eko; Rolia, Eva (Universitas Mandala Waluya, 2025)
This study used a descriptive qualitative approach with the aim of evaluating the implementation of the Hospital Health Promotion Programme (PKRS) at RSUD Jenderal Ahmad Yani Metro City in 2024. The research sample consisted of 8 informants selected using purposive sampling technique, which included 1 Head of PKRS Installation, 3 medical staff, and 4 patients. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation. Analysis was conducted using a thematic analysis approach. The results showed that the implementation of the Hospital Health Promotion Programme (PKRS) at RSUD Jenderal Ahmad Yani Metro City still faces obstacles, such as the lack of structured training for medical and non-medical staff, the non-integration of the PKRS programme in all hospital service lines, and the absence of structured ongoing evaluation. Strengthening the use of educational media, coordination between departments, and increasing the budget to support CSE activities are also needed. It is expected to improve service quality, reduce nosocomial infection rates, and strengthen public awareness of the importance of Clean and Healthy Living Behaviour (PHBS) in providing superior health services.